2014
DOI: 10.1371/journal.ppat.1004082
|View full text |Cite
|
Sign up to set email alerts
|

HIV and HCV Activate the Inflammasome in Monocytes and Macrophages via Endosomal Toll-Like Receptors without Induction of Type 1 Interferon

Abstract: Innate immune sensing of viral infection results in type I interferon (IFN) production and inflammasome activation. Type I IFNs, primarily IFN-α and IFN-β, are produced by all cell types upon virus infection and promote an antiviral state in surrounding cells by inducing the expression of IFN-stimulated genes. Type I IFN production is mediated by Toll-like receptor (TLR) 3 in HCV infected hepatocytes. Type I IFNs are also produced by plasmacytoid dendritic cells (pDC) after sensing of HIV and HCV through TLR7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
153
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(165 citation statements)
references
References 33 publications
9
153
1
2
Order By: Relevance
“…Moreover, the stimulation of TLR8 by HIV-1 single-stranded RNA has been reported to promote TNF release in human macrophages (57). Although we did not observe a type-I IFN response in virus-infected MDMs (data not shown), it has been shown that HIV-1 can activate the inflammasome in monocytes and macrophages via endosomal TLRs without induction of type-I IFN, a process leading to secretion of proinflammatory cytokines such as IL-1b and IL-18 (58). Therefore, we investigated whether endosomal TLRs could be involved in the HIV-1-mediated induction of BAFF secretion by MDMs.…”
Section: Endosomal Tlr Sensing Of Hiv-1 Is Not Involved In Baff Upregmentioning
confidence: 55%
See 2 more Smart Citations
“…Moreover, the stimulation of TLR8 by HIV-1 single-stranded RNA has been reported to promote TNF release in human macrophages (57). Although we did not observe a type-I IFN response in virus-infected MDMs (data not shown), it has been shown that HIV-1 can activate the inflammasome in monocytes and macrophages via endosomal TLRs without induction of type-I IFN, a process leading to secretion of proinflammatory cytokines such as IL-1b and IL-18 (58). Therefore, we investigated whether endosomal TLRs could be involved in the HIV-1-mediated induction of BAFF secretion by MDMs.…”
Section: Endosomal Tlr Sensing Of Hiv-1 Is Not Involved In Baff Upregmentioning
confidence: 55%
“…A previous study reported that HIV-1 can activate the inflammasome in monocytes and macrophages via endosomal TLRs without the induction of type-I IFN (58). We postulated that HIV-1 could drive BAFF secretion in macrophages by exploiting this pathway.…”
Section: Hiv-1-mediated Baff Induction Is Modulated By the Macrophagementioning
confidence: 86%
See 1 more Smart Citation
“…At present, five main classes of PRRs have been identified: TLRs, retinoic acid inducible gene-I (RIG-I)-like receptors, nucleotidebinding domain/leucine-rich repeat (LRR)-containing receptors (NLRs), C-type lectin receptors, and PYRIN-HIN domain containing family member (including absent in melanoma 2) (3). It has been described that DEAD/H-box helicase family members (e.g., RIG-I, MDA5, DHX36, and DHX33) (4-6), TLRs (e.g., TLR2, TLR3, TLR4, and TLR7) (7)(8)(9)(10), and NLRs (e.g., NLRX1, NLRP1, and NLPR3) (11)(12)(13) are involved in type I IFN production or inflammatory responses.…”
mentioning
confidence: 99%
“…HIV BaL and HIV IIIB were obtained from Joel Blankson and from Suzanne Gartner (University of Maryland, College Park, Maryland, USA), respectively, and expanded as previously described (18). In brief, 10 to 20 × 10 6 PHA-activated CD4 + T cells were spinoculated (1,200 g, room temperature, 2 hours) with 0.5 to 1 μg of HIV p24.…”
Section: Methodsmentioning
confidence: 99%